Healthcare Associated Infections In The National Institute Of Maternal And Perinatal Health - Gonzales-Carrillo, Oswaldo (2016)
Objective: To determine the prevalence and incidence rates of Healthcare Associated Infections (IAAS) in the NationalInstitute of Maternal and Perinatal Health (INMP) from 2012 to 2016. Materials and methods: We reviewed the cases of IAASin a historical cohort from 2012 to 2016, the case definition of IAAS or intrahospital Infection (IIH) was performed accordingto the Technical Standard of MINSA. The prevalence was established comparing it with the total of hospital discharges duringthe study period. The average incidence rates were established for each type of infection, according to risk factor of exposureand service of occurrence. These rates were compared with the national incidence rates established by the National Centerfor Epidemiology, Prevention and Control of Infections of MINSA - Peru.